Optimization strategies toward functional sodium-ion batteries - Chen, Jingwei (2023)
Exploration of alternative energy storage systems has been more than necessary in view of the supply risks haunting lithium-ion batteries. Among various alternative electrochemical energy storage devices, sodium-ion battery outstands with advantages of cost-effectiveness and comparable energy density with lithium-ion batteries. Thanks to the similar electrochemical mechanism, the research and development of lithium-ion batteries have forged a solid foundation for sodium-ion battery explorations. Advancements in sodium-ion batteries have been witnessed in terms of superior electrochemical performance and broader application scenarios. Here, the strategies adopted to optimize the battery components (cathode, anode, electrolyte, separator, binder, current collector, etc.) and the cost, safety, and commercialization issues in sodium-ion batteries are summarized and discussed. Based on these optimization strategies, assembly of functional (flexible, stretchable, self-healable, and self-chargeable) and integrated sodium-ion batteries (−actuators, −sensors, electrochromic, etc.) have been realized. Despite these achievements, challenges including energy density, scalability, trade-off between energy density and functionality, cost, etc. are to be addressed for sodium-ion battery commercialization. This review aims at providing an overview of the up-to-date achievements in sodium-ion batteries and serves to inspire more efforts in designing upgraded sodium-ion batteries.